Characterization and myocarditic capabilities of coxsackievirus B3 variants in selected mouse strains. - Gauntt, C J (1984)
Two variants of coxsackievirus B3 (CVB3) were compared with the original myocarditic parent variant (CVB3m) for myocarditic properties in several strains of mice. The ts1R variant produced little to no myocarditis in any of the nine mouse strains examined. The ts10R variant and CVB3m could be differentiated on the basis of the extent of myocarditis induced in mice of selected H-2b and H-2k haplotypes and in the female versus the male responses of two other inbred strains. Virus quantities recovered from the hearts of myocarditic mice did not correlate with the extent of disease. The three variants could not be differentiated on the basis of: (i) rate and extent of adsorption to heart tissue homogenates, (ii) kinetic neutralization rates with antiserum directed against CVB3m, (iii) 125I labeling of surface regions of polypeptides on purified particles, or (iv) rates of heat inactivation of infectivity at 50 degrees C. These data suggest that differences in pathogenicity cannot be attributed to major alterations in capsid polypeptides. Oligonucleotide fingerprint maps of T1 RNase digests of the genomes of purified particles of the three CVB3 variants showed distinct differences. Thus, the extent of myocarditis induced by CVB3 variants in a mouse model is affected by some subtle expression of the genome, presumably not involving capsid polypeptides, as well as by the haplotype and sex of a given mouse host species.